Thus spoke Galileo : the great scientist's ideas and their relevance to the present day - Galilei, Galileo, 1564-1642.; Frova, Andrea, 1936-; Marenzana, Mariapiera (New York : Oxford University Press, 2006)
A collection of writings in which Galileo Galilei reflects on the beliefs and experiences that have shaped his life and his impressions of the world surrounding him.
Translation of: Parola di Galileo.
Includes bibliographical references (p. [480]-484) and index.
Adult
Keywords: Galilei, Galileo, -- 1564-1642.; Galileo, -- 1564-1642.; Astronomy -- Early works to 1800.; Science -- Early works to 1800.; Scientists -- Italy; Astronomy -- Early works to 1800.; Science -- Early works to 1800.; Scientists -- Italy